Understanding violence and abuse: an anti-oppressive practice perspective - Fraser, Heather (Fernwood Publishing, 2017)
"In Understanding Violence and Abuse, Heather Fraser and Kate Seymour examine violence and abuse from an anti-oppressive practice perspective and make connections between interpersonal violence and structural, institutional and cultural violence. Using case studies from Canada, the U.K., the U.S., Australia, Bangladesh, India and elsewhere, the authors discuss topics ranging from class oppression, street violence, white privilege, war, shame, religious phobia and abuse in intimate relationships, as well as introduce the core tenets of anti-oppressive social work practice. They encourage readers to reflect upon hierarchies of identity and difference in relation to the ways in which violence and abuse are defined, understood and addressed. Further, they discuss several responses to violence using an anti-oppressive framework."--